The Vocabulary-Reading Link in Grade 7 Students - Lubguban, Kris Darlin; Sedillo, Eugenia (Journal of Interdisciplinary Perspectives, 2024)
Vocabulary mastery plays a critical role in language development. This study examined the relationship between vocabulary mastery and reading competence among Grade 7 students. A descriptive-correlational research design was utilized, with data collected through a survey questionnaire. Systematic sampling was employed to select 180 students from three secondary schools in District 10 of the Bayawan City Division. The study assessed vocabulary mastery in terms of meaning, grammar, spelling, and pronunciation, while reading competence was evaluated through word recognition level assessments. The results indicated significant variability in vocabulary mastery. Comprehension was the most challenging area, with most students categorized as "Did Not Meet Expectations." Conversely, pronunciation was the strongest skill, with the majority achieving "Satisfactory" results. Grammar and spelling scores were categorized as "Fairly Satisfactory." Additionally, a substantial portion of students demonstrated frustration-level reading competence. Crucially, the study found a strong correlation between vocabulary mastery and reading competence, underscoring their interdependence. These findings suggest that targeted interventions focusing on vocabulary development can significantly enhance the reading skills of Grade 7 students, ultimately leading to greater language proficiency and academic achievement. The results also highlight the importance of early implementation of vocabulary development programs to potentially prevent reading difficulties by Grade 7.